Blood Transfusion is Associated With Adverse Outcomes in Pediatric Solid Tumor Oncology Patients Following Tumor Resection. Issue 3 (22nd August 2022) - Acker, Shannon N.; Nolan, Margo M.; Prendergast, Connor; Lyttle, Bailey; Fares, Souha; Bensard, Denis D.; Partrick, David A.
Abstract : Background: Packed red blood cell (PRBC) transfusion is a lifesaving intervention that also has proinflammatory and immunosuppressive effects. Adults with a malignancy who receive PRBC transfusion have increased rates of infection, tumor recurrence, and decreased survival. The effect of PRBC transfusion among children with solid tumors is unknown. Methods: We performed a retrospective review of all children who underwent operative resection of a solid tumor malignancy. Data collected included demographic information, location of operation, nadir hemoglobin, and any PRBC transfusion within 30 days of tumor resection. Results: Three hundred sixty children underwent tumor resection at our institution between 2002 and 2013; 194 (54%) received a perioperative blood transfusion. After adjusting for stage at diagnosis, tumor location, preoperative chemotherapy and nadir hemoglobin, blood transfusion was associated with a higher rate of postoperative infectious complications, shorter disease-free interval, and a higher rate of tumor recurrence. Each additional transfused unit increased the risk of postoperative infection (odds ratio 3.83; 95% confidence interval 1.21, 14.22, P =0.031). Conclusions: Among children with solid tumor malignancies, PRBC transfusion within 30 days of operation is associated with higher rates of postoperative infection. If transfusion becomes necessary, single unit increments should be transfused. Level of Evidence: Level III.